A Buddhist Model for Health Promotion in Preventing Drinking and Smoking Among Thai Youth - Suwanprateep, Thanee; Kantatian, Wutthinant; Maijandee, Phongphat (Journal of Buddhist Studies Chulalongkorn University, 2022)
The purpose of this research is to study the application of Buddhist teachings to prevent alcohol consumption and smoking among Thai youths, and to present a Buddhist model of well-being promotion to prevent alcohol consumption and smoking among the same group. This is achieved through qualitative research consisting of documentary research and in-depth interviews with samples of 40 youths from the four regions. The study found that a reflection on Buddhist concepts and principles revealed an emphasis on the human mind, whose functioning process is more powerful than that of the body. Therefore, it is of utmost importance to start with the youths’ “mind."The principle of "Yonisomanasikara" leads the youths to wisdom: correct perception, attitudes and beliefs, and discrimination of good and bad. The principles of "Paratoghosa/Kalyanamitra" help the youths to foster love and confidence in distancing themselves from alcohol and cigarettes. These two principles combined resulted in a Buddhist well-being promotion model based on the youths themselves and on external environmental factors. The youths can be shaped by good living models and moving experiences from close relations. This should be reinforced with a symbolic model – the reflection from the two principles of Buddhist teaching – which enables the youths to believe in their capacities to control themselves.